Development of solar energy and present policies in Malaysia - Solangi, K.H.; Lwin, T.N.W.; Rahim, N.A.; Hossain, M.S.; Saidur, Rahman; Fayaz, H. (2011)
Solar energy is regarded a clean renewable energy source, with great potential for environment-friendly electricity generation. Properly harvested, it can optimally benefit. Malaysia has a particularly abundant source of renewable energies; for solar, as evidenced by a 4.21kWh/m2 to 5.56kWh/m2 average daily radiation with a high of 6.8kWh/m 2 (purportedly in August and November). Present installed capacity totaling 20,493MW, is estimated to reach 23,099MW maximum-demand capacity in 2020, by when 190MWp of cumulative solar energy would have been installed. Incentives should be offered to boost solar energy's economic feasibility. This paper examines the Malaysian government's various policies on, and implementation of, solar energy technology. It suggests methods and policies for provision of safe, cost-effective, quality energy, and discusses environmental sustainability and diversification of solar energy resource.